Pengembangan Nasi Sorgum Instan dengan Teknologi Fluidized Bed Dryer dan Penambahan Gliserol - Purwaningrum, Bunga Ayu; Taqi, Fahim Muchammad; Muhandri, Tjahja; Saraswati, Saraswati (Jurnal Teknologi dan Industri Pangan, 2025)
Instant sorghum rice is produced through cooking, freezing, and drying processes, resulting in a porous structure that allows for easy rehydration. This research aimed at developing an alternative method for instantizing sorghum rice using a combination of fluidized bed dryer (FBD) technique and glycerol addition. The samples were evaluated, including physical characteristics, consumer acceptance, and nutritional value information of selected product. Sorghum seeds were polished for 30, 45, and 60 sec, and their whiteness degree was recorded. Subsequently, the seeds were washed, pre-cooked with the addition of glycerol (0, 2, and 4%), steamed, frozen, and finally dried. The cooked sorghum rice was frozen in a freezer for 24 h at -20 °C and dried with a fluidized bed dryer until a constant weight was achieved. The addition of glycerol did not affect panelist’s acceptance for color, texture, taste, aroma and overall attributes (at significance level of 5%), and therefore, the treatment without glycerol was selected for further steps. The selected treatment exhibited the physical characteristics as follow: rehydration time (7.5 min), bulk density (0.41±0.03 g/mL), water absorption (41.92±0.50%), rehydration ratio (3.58±0.02) and volume expansion ratio (223.72±12.94), indicating that it meets the criteria for instant food. The nutritional value per 60 g serving size was as follows: total energy (240 kcal), protein 3 g (6% of Recommended Dietary Allowance (RDA)), total fat 0 g (0% RDA) and carbohydrate 56 g (17% RDA).